2015
DOI: 10.1016/j.ypmed.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration and adult weight gain in the National Survey of American Life (NSAL)

Abstract: The United States has the unenviable distinction of having both the highest obesity rate among Organisation for Economic Co-operation and Development (OECD) member countries and the highest incarceration rate in the world. Further, both are socially patterned by race/ethnicity and socioeconomic position. Incarceration involves various health behaviors that could influence adult weight trajectory. We evaluated the associations between history and duration of adult incarceration and weight gain using the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…As such, experiencing a family disruption firsthand because a relative is in jail or prison creates compounding difficulties from which Black people, families, and communities may never recover. Findings reported here and elsewhere 12,[22][23][24][25]27,30,32 confirm that the incarceration of Black men should be considered a public health crisis.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As such, experiencing a family disruption firsthand because a relative is in jail or prison creates compounding difficulties from which Black people, families, and communities may never recover. Findings reported here and elsewhere 12,[22][23][24][25]27,30,32 confirm that the incarceration of Black men should be considered a public health crisis.…”
Section: Resultssupporting
confidence: 80%
“…Consistent with Model 1, former incarceration negatively associated with obesity, replicating findings reported by Bailey et al who used the same data as this study. 27 This salutogenic effect may be a function of cigarette smoking, 23 which may start in jail or prison and tends to suppress weight gain, but evidence that the culprit is cigarette smoking is equivocal. 27 …”
Section: Incarceration and Obesity -Brown Et Almentioning
confidence: 99%
“…In this study, the SSF figures identified by women as representing them before imprisonment were, in most cases, smaller bodies than those identified to represent their current body, revealing their perception of weight gain during incarceration. Weight gain was also high in other studies with inmates [11,12,15,16], being more prevalent in women [16,17]. This phenomenon may be related to inadequate diet with low consumption of healthy foods and high consumption of industrialized food, sedentary life style, without working programs or recreational and physical activities, depression or even drug abstinence, and the use of atypical antipsychotic medications [6,[9][10][11]15,16,18].…”
Section: Discussionmentioning
confidence: 89%
“…Some of this work has documented incarceration as an independent risk factor for unhealthy weight status as well as chronic disease burden. Other recent work, for example Bailey et al [14] study, demonstrate a more complex relationship between incarceration and health status, including obesity. Their work, which contradicts the body of literature cited above, shows an inverse association between incarceration and adult weight gain for men, especially African American men and may point to a protective effect of incarceration for vulnerable populations [14].…”
Section: Introductionmentioning
confidence: 80%